Hybrid input-output analysis of embodied energy security - Shepard, Jun U. (Appl Energy, 2020)
National energy security depends on a stable network of international trade in not only primary energy (e.g., crude oil and natural gas) and secondary energy (electricity), but also embodied energy. The latter consists of both direct energy used to directly produce a final good (e.g., crude oil used to make synthetic rubber), and indirect energy incorporated in intermediate goods and services used to make a final product (e.g., coal used to smelt iron into steel that goes into the frames of cars). While studies have analyzed international trade in embodied energy, the global flow of the indirect component of this energy has not been explicitly examined. Here we develop and apply a new hybrid input-output database of energy flows within and among the world’s largest 136 economies so as to compare and contrast energy security metrics of indirect energy against direct energy. We find that 23% of the world’s embodied energy network is comprised of trade linkages in indirect energy between primary energy producing countries and other countries with which they do not have direct trade ties. We also find that the global economy is 90% more dependent on imports of indirect energy than direct energy and, unsurprisingly, that countries generally have many more trading partners in indirect energy than they do in direct energy. These differences in energy security metrics are assessed at the global, sectoral, and national levels over the years 2000–2015. The differences point to critical intermediary country nodes in the global trade network of indirect energy, principally the United States, China, and Russia.